Effect of potassium fertilization in 'Rica' guava (Psidium guajava) cultivation - Natale, W.; Coutinho, ELM; Boaretto, A. E.; Pereira, F. M. (Indian Counc Agricultural Res, 1996)
A field experiment was conducted from 1989-90 to 1991-92 to study the effect of potassium fertilization on guava (Psidium guajava L.). using 1-year-old plants of 'Rica', grown in a Kanhapludalf soil in the Jaboticabal region in Brazil. During the first year the K doses used were: 0, 24.9, 49.8, 99.6, 149.4 and 199.2 g K/plant, which were doubled during the second year and tripled during the third. In the third year the increase in g level showed positive response in yield. About 90% of the maximum yield observed was associated with 527 g K/plant and with a leaf content of 18.9 g K/kg.